A Double Disturbed Lunar Plasma Wake. Issue 2 (27th January 2021) - Rasca, A. P.; Fatemi, S.; Farrell, W. M.; Poppe, A. R.; Zheng, Y.
Abstract: Under nominal solar wind conditions, a tenuous wake forms downstream of the lunar nightside. However, the lunar plasma environment undergoes a transformation as the Moon passes through the Earth's magnetotail, with hot subsonic plasma causing the wake structure to disappear. We investigate the lunar wake response during a passing coronal mass ejection (CME) on March 8, 2012 while crossing the Earth's magnetotail using both a magnetohydrodynamic (MHD) model of the terrestrial magnetosphere and a three‐dimensional hybrid plasma model of the lunar wake. The CME arrives at 1 AU around 10:30 UT and its impact is first detected inside the geomagnetic tail after 11:10 UT by the Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (THEMIS‐ARTEMIS) satellites in lunar orbit. A global magnetospheric MHD simulation using Wind data for upstream conditions with the OpenGGCM model reveals the magnetosheath compression to the lunar position from 11:20–12:00 UT, accompanied by multiple flux rope or plasmoid‐like features developing and propagating tailward. MHD results support plasma changes observed by the THEMIS‐ARTEMIS satellites. Lunar‐scale simulations using the Amitis hybrid code show a short and misaligned plasma wake during the Moon's brief entry into the magnetosheath at 11:20 UT, with plasma expansion into the void being aided by the higher plasma temperatures. Sharply accelerated flow speed and a compressed magnetic field lead to an enhanced electric field in the lunar wake capable of generating sudden changes to the nightside near‐surface electric potential. Key Points: Passing coronal mass ejection (CME) during a Full Moon distorts the magnetopause and magnetosheath, resulting in the Moon's removal from the geomagnetic tail CME arrival results in the redevelopment of a short optically misaligned lunar plasma wake Event conditions are favorable for the development of flux‐rope like plasmoids in the magnetotail capable of being detected at the Moon